2016
DOI: 10.1103/physrevb.93.041403
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous ballistic transport in disordered bilayer graphene: A Dirac semimetal induced by dimer vacancies

Abstract: We report anomalous quantum transport features in bilayer graphene in the presence of a random distribution of structural vacancies. By using an efficient real-space Kubo-Greenwood transport methodology, the impact of a varying density of dimer versus nondimer vacancies is investigated in very large scale disordered models. While nondimer vacancies are shown to induce localization regimes, dimer vacancies result in an unexpected ballistic regime whose energy window surprisingly enlarges with increasing impurit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…This is reminiscent of the midgap state produced by asymmetry between the number of atoms A and B in monolayer graphene [41,14]. In agreement with previous findings for MLG [4,14,16,20] and BLG [12,29,32], for large values of energies E the DOS is weakly affected by the presence of disorder. Finally near the Dirac energy there is an intermediate regime where the pseudo-gap is filled ("plateau").…”
Section: Density Of Statessupporting
confidence: 91%
See 3 more Smart Citations
“…This is reminiscent of the midgap state produced by asymmetry between the number of atoms A and B in monolayer graphene [41,14]. In agreement with previous findings for MLG [4,14,16,20] and BLG [12,29,32], for large values of energies E the DOS is weakly affected by the presence of disorder. Finally near the Dirac energy there is an intermediate regime where the pseudo-gap is filled ("plateau").…”
Section: Density Of Statessupporting
confidence: 91%
“…[14,15,16,17,18,19,20,21,22,23,24,25] and Refs. therein), and for BLG [26,27,28,29,30,31,32,12]. Most of them consider a standard Hamil-tonian that takes only into account the hopping between the nearest neighbors orbitals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We attribute this behavior to enhanced quantum correction induced by electron-hole interactions. PACS numbers: 71.35.-y, 64.70.Tg, 31.15.V-, 71.35.CcIntroduction.-Recent experiments have shown that most correlated materials contain a significant amount of defects, which appear to be intrinsic [1][2][3][4][5][6][7]. These inhomogeneities could significantly affect device performance.…”
mentioning
confidence: 99%